Ship or sheep? : an intermediate pronunciation course : [student's book] - Baker, Ann. (Cambridge ; New York : Cambridge University Press, 1981)
This is a comprehensive pronunciation course for intermediate students of English. It provides systematic practice of English pronunciation, stress and intonation through a wide variety of interesting exercises and activities.
Keywords: English language; Pronunciation; English language -- Pronunciation; English language -- Sound recordings for foreign speakers